APPLICATION OF GEOELECTRICAL METHOD FOR GROUNDWATER EXPLORATION IN SUKACAI VILLAGE, JIPUT – PANDEGLANG, BANTEN PROVINCE - Rosmalia Dita Nugraheni; Mohammad Apriniyadi; Muhammad Burhannudinnur; Suherman Dwi Nuryana; Benyamin Benyamin (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2019)
The increasing number of inhabitant in Sukacai village, Jiput – Pandeglang leads to the risen of clean water demand. However, along with the raising of demand, the groundwater availability has decreased. During the dry season, the water quality is poor and the rate of flow tends to be critical. As a consequence, the community is suffering from the scarcity of clean water supply for daily consumption and household necessity. This community service program aims to fulfill the needs of groundwater supply by applying the geophysical method, to recommend the depth of aquifer and construct the well of groundwater. The method is carried out using geo-electrical instruments to reveal the depth of aquifer as the source of groundwater. Another social approach is performed by educating the community about the optimization of well construction, as well as the effect of shallow and deep well construction towards the rate and quality of groundwater. The session has been wrapped with sharing and discussion. As a result, the authors recommend the depth of well construction is approximately 20 m for shallow well and 50 m for moderate well. The moderate well option is more recommended to avoid any contamination of pollution source as well as to maintain the flow rate during dry season.